Comparing levels of psychological stress and its inducing factors among medical students. Issue 6 (December 2019) - Rafique, Nazish; Al-Asoom, Lubna I.; Latif, Rabia; Al Sunni, Ahmed; Wasi, Samina
الملخص: أهداف البحث: تهدف هذه الدراسة إلى تحديد ومقارنة مستويات الإجهاد النفسي لدى طلاب الطب من السنة الأولى إلى السنة الخامسة، ومعرفة العوامل المسببة للإجهاد. طرق البحث: أجريت هذه الدراسة المستعرضة على ٤٦٨ من الإناث. استخدمت الدراسة أداة قياس الإجهاد النفسي "كسلر ١٠"، واستبانة حول مختلف العوامل التي تسبب الإجهاد. النتائج: أبلغ ٦٧.٩ ٪ من الطالبات عن وجود الإجهاد الفسيولوجي لديهن. وبلغت نسبة الطالبات بدون إجهاد، وبإجهاد خفيف، وإجهاد معتدل، وإجهاد شديد ٣٢٪ و٢٤٪ و٢٢٪ و٢١.٨٪ على التوالي. وكان أعلى معدل انتشار للإجهاد الفسيولوجي عند طالبات السنة الأولى (٨٢.٦٪). وانخفضت درجات التوتر بشكل ملحوظ مع زيادة في السنة الدراسية، باستثناء السنة الأخيرة. وتضمنت متغيرات الدراسة السنة الأولى من الدراسة الطبية (٠.٠٢٢)، والإجهاد الأكاديمي (٠.٠٠١)، ووجود مشكلة جسدية (٠.٠٠١) والزواج (٠.٠٠٢)، وكانت عوامل الخطر المستقلة لارتفاع التوتر الملحوظ (درجة كسلر ١٠ > ٢٤). واستشار ١١.١٪ من الطالبات طبيب فيزيائي، في حين أن ٣.٤٪ من الطالبات يتناولن بعض الأدوية لعلاج الإجهاد. الاستنتاجات: خلصت الدراسة إلى أن السنة الأولى من الدراسة الطبية، والإجهاد الأكاديمي، ووجود مشكلة جسدية والزواج هي عوامل خطر مستقلة لارتفاع نسبة انتشار الإجهاد النفسي. نوصي بأن يكون فحص الإجهاد النفسي إلزاميا في كليات الطب. ويفضل أن يتكرر كل ستة أشهر، كما يجب تقديم المشورة لمن لديه إجهاد نفسي، وتقديم خدمات الصحة النفسية والمتابعة السليمة. Abstract: Objective: This study aimed to determine and compare degrees of psychological stress and inducing factors thereof among first to fifth year medical students (MS). Methods: This cross-sectional study was conducted on 468 female MS. We used the Kessler 10 Psychological Distress Inventory consisting of questions on a range of stress-inducing factors. Results: A total of 67.9% students reported physiological stress. The percentage of MS without stress and with mild, moderate, and severe stress was 32%, 24%, 22%, and 21.8%, respectively. The highest prevalence of physiological stress was found among first-year students (82.6%). Stress scores significantly decreased with advancement in the year of study, except for the final year (p = 0.001). We found that the first year of medical studies (0.022), academic stress (0.001), the presence of a physical problem (0.001), and being married (0.002) were independent risk factors for high perceived stress (HPS), as shown by K10 scores >24. A total of 11.1% students consulted a psychiatrist, whereas 3.4% admitted taking some medication for stress. Conclusion: This study infers that the first year of medical studies, academic stress, the presence of a physical problem, and being married are independent risk factors for HPS. We recommend mandatory stress screening for MS in all medical colleges. Ideally, the screening should be repeated every six months and students identified as having HPS should be provided with counselling, mental health services, and a proper follow-up.